2008
DOI: 10.1080/00405000701476351
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of cellulase enzyme in biopolishing application of cotton fabrics

Abstract: Immobilization of commercial cellulase enzyme on ion exchange and epoxy resin carriers has been studied under various process parameters and conditions by using methanol to allow reuse of cellulase enzyme that would otherwise be discarded after biopolishing. The activity of immobilized enzyme was determined by measuring the amount of glucose made from carboxy methyl cellulose by using an assay with reading at 492 nm. The retained activity was investigated by cellulase assay for every successive cycle of operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…The industrial enzymatic treatment of cellulosic textile materials with cellulases is applied in two major procedures, that is bio‐polishing and bio‐stonewashing 1–3. In industrial applications, low cellulase concentrations and treatment times are usually used to randomly modify the fibers1, 2, 4 and it has been shown that 5% weight loss of fibers in cellulase modification is enough for bio‐polishing purposes. Cellulase enzyme treatment of cellulosic substrates has been studied extensively and the kinetics of the reaction as well as the role of reaction's parameters is well‐known 5–9.…”
Section: Introductionmentioning
confidence: 99%
“…The industrial enzymatic treatment of cellulosic textile materials with cellulases is applied in two major procedures, that is bio‐polishing and bio‐stonewashing 1–3. In industrial applications, low cellulase concentrations and treatment times are usually used to randomly modify the fibers1, 2, 4 and it has been shown that 5% weight loss of fibers in cellulase modification is enough for bio‐polishing purposes. Cellulase enzyme treatment of cellulosic substrates has been studied extensively and the kinetics of the reaction as well as the role of reaction's parameters is well‐known 5–9.…”
Section: Introductionmentioning
confidence: 99%
“…For bio polishing acid and neutral cellulases bath is maintained at 4.5-5.5 and 7 respectively, the process is heated at 55 o C. Finally, the process is terminated at the temperature 85 o C. The immobilization of cellulase can restrict its action to fiber surface. Various immobilization of cellulases enzyme methods improve thermal stability and reusability [125].…”
Section: Bio-polishingmentioning
confidence: 99%
“…Pamuklu ve pamuklu karýþým materyallerinin terbiyesinde genel olarak kullanýlan enzimler; amilaz, proteaz, selülaz, pektinaz, lipaz, katalaz ve lakkazdýr. Kullanýlan bu enzimler, materyalde, haþýl sökme, hidrofilleþtirme, yumuþatma, biyoparlatma, denim yýkama ve diðer çeþitli etkileri saðlamak amacýyla kullanýlmaktadýr [11]. Kullanýldýðý materyallere tutum, görünüm ve diðer yüzey karakteristiklerini geliþtirme gibi avantajlar saðlamaktadýr [3,12].…”
Section: Gýrýþunclassified